Answer:
2x+8
2 is common
2(x+4)=0
Step-by-step explanation:
Answer:
B.False
Step-by-step explanation:
Because it built different
I'm assuming all of (x^2+9) is in the denominator. If that assumption is correct, then,
One possible answer is ![f(x) = \frac{4}{x}, \ \ g(x) = x^2+9](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7B4%7D%7Bx%7D%2C%20%20%5C%20%5C%20g%28x%29%20%3D%20x%5E2%2B9)
Another possible answer is ![f(x) = \frac{4}{x+9}, \ \ g(x) = x^2](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7B4%7D%7Bx%2B9%7D%2C%20%5C%20%5C%20g%28x%29%20%3D%20x%5E2)
There are many ways to do this. The idea is that when we have f( g(x) ), we basically replace every x in f(x) with g(x)
So in the first example above, we would have
![f(x) = \frac{4}{x}\\\\f( g(x) ) = \frac{4}{g(x)}\\\\f( g(x) ) = \frac{4}{x^2+9}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7B4%7D%7Bx%7D%5C%5C%5C%5Cf%28%20g%28x%29%20%29%20%3D%20%5Cfrac%7B4%7D%7Bg%28x%29%7D%5C%5C%5C%5Cf%28%20g%28x%29%20%29%20%3D%20%5Cfrac%7B4%7D%7Bx%5E2%2B9%7D)
In that third step, g(x) was replaced with x^2+9 since g(x) = x^2+9.
Similar steps will happen with the second example as well (when g(x) = x^2)
Answer:
6
Step-by-step explanation:
put unknown as y
area of rectangle = width × long
y(y - 2)=48
y² -2y =48
u can use scientific calculator to find this
y²-2y-48=0
(y-8)(y+6)=0
y=8 y=-6
take the positive value and ignore the negative value
width=y-2 long=8
8-2=6
I hope this help you :)